2017
DOI: 10.1007/s10620-017-4460-y
|View full text |Cite
|
Sign up to set email alerts
|

Fukuoka and AGA Criteria Have Superior Diagnostic Accuracy for Advanced Cystic Neoplasms than Sendai Criteria

Abstract: In a surgical series of patients with pancreatic cysts, the AGA and Fukuoka criteria had superior diagnostic accuracy for advanced neoplastic cysts compared to the original Sendai criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Regarding the “ worrisome ” criteria, both guidelines had similar sensitivity. Overall, the FCG had a better performance than the SCG in predicting advanced neoplasia, which is consistent with the conclusions in most published articles . In addition, individual preference for the surgical resection of cysts is acceptable in our institution, which is mainly derived from abdominal discomfort.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the “ worrisome ” criteria, both guidelines had similar sensitivity. Overall, the FCG had a better performance than the SCG in predicting advanced neoplasia, which is consistent with the conclusions in most published articles . In addition, individual preference for the surgical resection of cysts is acceptable in our institution, which is mainly derived from abdominal discomfort.…”
Section: Discussionsupporting
confidence: 89%
“…Changes in guidelines have improved identification of advanced neoplasia in IPMNs. Sighinolfi et al[ 13 ] retrospectively validated the 2006 ICG, 2012 ICG, and AGA criteria, where the 2012 ICG and AGA showed significantly improved specificity (58.2% and 62.4%, respectively) and diagnostic accuracy (67% and 68%, respectively) for advanced neoplasia compared to the 2006 ICG (specificity 32.7%, diagnostic accuracy 46%)[ 13 ]. Additionally, Kang et al[ 14 ] have demonstrated superior diagnostic performance of the 2017 ICG [area under the curve (AUC) 0.78] compared to 2012 ICG criteria (AUC 0.74) for the detection of malignancy in BD-or mixed-type IPMNs[ 14 ].…”
Section: How Do the Guidelines Perform?mentioning
confidence: 99%
“…The Sendai guidelines were revised in 2010 at the 13th Congress of the IAP in Fukuoka, Japan. This resulted in the publication of updated 2012 Fukuoka guidelines with revised criteria for imaging surveillance and surgical resection of branch duct IPMN 21 . Moreover, the Fukuoka guidelines incorporated the use of EUS‐FNA for cysts larger than or equal to 3 cm or smaller cyst's with pancreatitis or ‘worrisome features’ on CT imaging; this was an attempt to further delineate risk prior to making a decision for surgical resection 7 …”
Section: Guidelinesmentioning
confidence: 99%